2020
DOI: 10.1111/jan.14625
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy of pregnant women and duration of breastfeeding maintenance: A feasibility study

Abstract: Aims: Research the association between health literacy (HL) and exclusive breastfeeding at 4-months postpartum. Background: Despite the benefits of breastfeeding (BF), its rates are low worldwide. Among the reasons for abandonment is the level of maternal education. Maternal education has been associated with HL, but evidence between HL and BF maintenance is limited. Design: A cross-sectional study. Methods: The sample compromised 229 nursing mothers recruited from January 2018 to the end of December 2018 at S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 55 publications
2
23
3
Order By: Relevance
“…Health literacy disease prevention scores of the mothers who had breastfed their babies for 12 months were found higher than those who had never breastfed or breastfed for more than 12 months. In conformity with our study, Vila-Candel et al have detected in their study that early cessation of breastfeeding was associated with low HL (17). In another research, it was defended that maternal health literacy must be improved to increase breastfeeding self-efficacy (18).…”
Section: Resultssupporting
confidence: 91%
“…Health literacy disease prevention scores of the mothers who had breastfed their babies for 12 months were found higher than those who had never breastfed or breastfed for more than 12 months. In conformity with our study, Vila-Candel et al have detected in their study that early cessation of breastfeeding was associated with low HL (17). In another research, it was defended that maternal health literacy must be improved to increase breastfeeding self-efficacy (18).…”
Section: Resultssupporting
confidence: 91%
“…Although it may seem that a low educational level could be associated with a low HL, this relationship does not always have to be observed [38]. A relation was also recently found between HL levels and continuing EBF in a pilot study; however, the follow-up period only covered 4 months [25]. Therefore, the present study verifies a statistically significant association between limited HL level and EBF cessation before 6 months in line with previous studies [27], and observed that the probability of EBF cessation was more than two-fold compared to the mothers with an adequate HL level.…”
Section: Discussionmentioning
confidence: 90%
“…We excluded women with cognitive impairments, language barriers, or illiteracy (not able to read). Illiterate women were excluded from the study as they would be unable to complete the self-administered health literacy screening tools [25]. Finally, we also excluded mothers who we were unreachable by telephone after three attempts at 6 months postpartum.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…All authors found positive correlations between HL and breastfeeding behavior, although the outcome breastfeeding was assessed differently in each study: feeding of a higher proportion of breastmilk than formula [Yin], a higher rate of exclusive breastfeeding shortly after birth [Stafford], and exclusive breastfeeding for more than 2 months [Kaufman] [11,12,14]. Vila-Candel et al found no statistical significant association between functional HL measured by newest vital sign (NVS) and exclusive breastfeeding for more than 4 months [34].…”
Section: Discussionmentioning
confidence: 99%